2005
DOI: 10.1007/s00384-005-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing anastomosis safety and preventing abdominal adhesion formation by the use of polypeptides in the rat

Abstract: Methods: An ileocolic anastomosis was performed under both "clean" and "septic"conditions in the rat. The treatment group received intraperitoneal poly-L-lysine and poly-Lglutamate while controls received sodium chloride. Abdominal adhesions, anastomosis leakage and burst pressure were analyzed after 1, 3, 5 and 7 days in the "clean" anastomosis model and after 7 days in the "septic" model.Results: A significant decrease (p<0.01) in the amount of adhesions was seen in animals treated with polypeptides after 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Postoperative adhesions in this study also significantly decreased, supporting our previous studies [11][12][13] . Bleeding per se do not cause development of adhesions, but is well known to predispose for adhesions with concurrent serosal injury [30] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Postoperative adhesions in this study also significantly decreased, supporting our previous studies [11][12][13] . Bleeding per se do not cause development of adhesions, but is well known to predispose for adhesions with concurrent serosal injury [30] .…”
Section: Discussionsupporting
confidence: 81%
“…We have in previous studies shown a significant antiadhesive effect by using a combination of two differently charged polypeptides, poly-L -lysine and poly-L -glutamate [11,12] , in a standardized animal model for abdominal adhesions [15] . In another study, we demonstrated an improved anastomotic healing in the colon as measured by anastomotic burst pressure with a continued positive effect on preventing postoperative adhesions [13] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The antiadhesive effect of the polypeptides is based on electrostatic binding between the strong cation poly-L-lysine and the negatively charged damaged peritoneum [29], and thereafter electrostatic bonds between the poly-L-lysine and the anion poly-L-glutamate create a mechanical barrier between damaged and adhesionprone peritoneal tissue. The polypeptide matrix accumulates in areas of damaged peritoneum [16] and has also been shown to aid in intestinal healing as well as decreasing parenchymal bleeding and possibly inflammation [17,18,30].…”
Section: Discussionmentioning
confidence: 99%
“…In previous experimental studies we have shown very promising results in the reduction of postoperative abdominal adhesions using a combination of differently charged polypeptides, α-poly-L-lysine and poly-L-glutamate [16][17][18]. The positively charged poly-L-lysine binds to the negatively charged damaged peritoneal surface and then attaches the negatively charged poly-Lglutamate to build a neutral matrix preventing adhesion formation [19].…”
Section: Introductionmentioning
confidence: 99%